2014
DOI: 10.4162/nrp.2014.8.6.713
|View full text |Cite
|
Sign up to set email alerts
|

High tendency to the substantial concern on body shape and eating disorders risk of the students majoring Nutrition or Sport Sciences

Abstract: BACKGROUND/OBJECTIVESStudies have indicated that university students majoring in nutrition and dietetics or sport sciences may have more obsessions associated with eating attitudes and body shape perception compared to other disciplines i.e. social sciences. Therefore, this study aimed to assess and compare the risk of eating disorders and body shape perception.MATERIALS/METHODSData was collected from 773 undergraduate students at the Departments of Nutrition and Dietetics (NDD) (n = 254), Physical Education a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
(50 reference statements)
2
10
0
4
Order By: Relevance
“…Previous studies have reported different tendency for abnormal eating behaviors or body concerns between health-related non-nutrition majors and nutrition major [19,39]. Therefore, current study distinguished these two groups and included three academic major groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported different tendency for abnormal eating behaviors or body concerns between health-related non-nutrition majors and nutrition major [19,39]. Therefore, current study distinguished these two groups and included three academic major groups.…”
Section: Methodsmentioning
confidence: 99%
“…In a study with data from 189 female Portuguese students aged 18–25 years old, there was no difference in risk of ED development between students majoring in nutrition and other health-related majors or non-health-related majors [18]. Another study collected data from 773 Turkish undergraduate students and reported that students studying Physical Education and Sports had a higher tendency for abnormal eating behavior and more concern for body shape than students studying Nutrition and Dietetics or Social Science [19]. In a cross-sectional comparison of nutrition students in Germany, nutrition students were inclined to restrict food intake for weight control; however, they did not display more disordered eating patterns compared to other students.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors found that the risk of eating disorders (Laus, Moreira, & Costa, 2009;Magdalena & Julie, 2012;Reinstein, Koszewski, Chamberlin, & Smith-Johnson, 1992;Rosales, Ruíz, Martínez, & Molina, 2012) or its prevalence (Worobey and Schoenfeld, 1999) is higher among nutrition and dietetics students when compared with students from other areas, while others haven't found significant differences between these two groups (Behar, Alviña, Medinell, & Tapia, 2007;Fiates & Salles, 2001;Fredenberg, Berglund, & Dieken, 1996;Harris, Gee, d'Acquisio, Ogan, & Pritchett, 2015;Kiziltan & Karabudak, 2008;Mealha, Ferreira, Guerra, & Ravasco, 2013;Santos, Meneguci & Mendonça, 2008;Torresani, 2003). On the other hand, some studies conclude that the predisposition of nutrition and dietetic students to eating disorders is even lower, when compared to medical (Mehr, Clemens, Roach, & Beech, 1997) or sports students (Nergiz-Unal, Bilgic, & Yabanci, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another study looking at body shape and weight concerns, by Nergiz-Unal et al [31], compared students of social sciences, physical education and nutrition. Physical education students achieved the highest scores in the test measuring posture habits (the Eating Attitudes Test -EAT-40), regardless of gender, and on the questionnaire measuring body focus (the Body Shape Questionnaire -BSQ-34).…”
Section: Discussionmentioning
confidence: 99%